Sustained Weight Loss with Vagal Nerve Blockade but Not with Sham: 18-Month Results of the ReCharge Trial - Scott A. Shikora; Bruce M. Wolfe; Caroline M. Apovian; Mehran Anvari; David B. Sarwer; Robert D. Gibbons; Sayeed Ikramuddin; Christopher J. Miller; Mark B. Knudson; Katherine S. Tweden; Michael G. Sarr; Charles J. Billington (Hindawi Limited, 2015)
Background/Objectives. Vagal block therapy (vBloc) is effective for moderate to severe obesity at one year. Subjects/Methods. The ReCharge trial is a double-blind, randomized controlled clinical trial of 239 participants with body mass index (BMI) of 40 to 45 kg/m or 35 to 40 kg/m with one or more obesity-related conditions. Interventions were implantation of either vBloc or Sham devices and weight management counseling. Mixed models assessed percent excess weight loss (%EWL) and total weight loss (%TWL) in intent-to-treat analyses. At 18 months, 142 (88%) vBloc and 64 (83%) Sham patients remained enrolled in the study. Results. 18-month weight loss was 23% EWL (8.8% TWL) for vBloc and 10% EWL (3.8% TWL) for Sham (P<0.0001). vBloc patients largely maintained 12-month weight loss of 26% EWL (9.7% TWL). Sham regained over 40% of the 17% EWL (6.4% TWL) by 18 months. Most weight regain preceded unblinding. Common adverse events of vBloc through 18 months were heartburn/dyspepsia and abdominal pain; 98% of events were reported as mild or moderate and 79% had resolved. Conclusions. Weight loss with vBloc was sustained through 18 months, while Sham regained weight between 12 and 18 months. vBloc is effective with a low rate of serious complications.